Um olhar através do visível: reflexões sobre as fotografias de Chema Madoz - Soares, Lílian de Carvalho (2011)
This study investigates the images of the contemporary Spanish photographer Chema Madoz. To this end, an analysis of his creation process was performed, embracing not only the classic steps of photography, but also the preparation of drawings and construction of peculiar things. Therewith, the photographer develops particular and poetic images that cast some doubt on the ontology of photography. In this sense, in developing the dissertation, the paradigms established on photographic language are re-discussed, in order to achieve the questions raised by his images. Then, we propose to think about his images from the entanglement with time, aiming to expand the understanding about his photography and raise the labyrinth of paradoxes, typical of his work. The aim is to show, then, that the photographs suggest a look beyond the visible